The uses of small talk in social work: Weather as a resource for informally pursuing institutional tasks. (November 2022) - Iversen, Clara; Flinkfeldt, Marie; Tuncer, Sylvaine; Laurier, Eric
Welfare organisations across the world are becoming more streamlined with less time for building relationships with clients, rendering non-governmental organisations increasingly important for welfare provision. In this paper, we investigate an understudied area in social work: the small talk through which volunteer organisations conduct social work tasks in interaction with clients. The data consist of 108 phone calls to a helpline that offers social contact to older people, recorded in 2020 in Sweden. We use conversation analysis to investigate how callers and call-takers rely on and produce informal sociability in providing support for clients. Specifically, we show that talk about the weather, a prosaic small talk topic, is interwoven with institutional work. By allowing or preventing outdoor activities, weather is a conduit for call-takers and callers to introduce and navigate norms of remaining active as an older adult. Cultural understandings and concerns about good or bad weather allow participants to move between reproducing client/service-provider asymmetries and reaching affiliative affective stances. Thus, the supposedly banal topic of the weather, known as a resource for sociability amongst the unacquainted, is, in this setting, used in ways particular to social work practice.